IGF-1 secreted by mesenchymal stem cells affects the function of lymphatic endothelial progenitor cells: a potential strategy for the treatment of lymphedema - Xue, Zekuan; Yang, Dongdong; Jin, Zhiwei; Li, Yijie; Yu, Yunfei; Zhao, Xinchun; Huang, Yongzhou; Jia, Shengqiu; Zhang, Tong; Huang, Guilin; Hou, Jixue (Frontiers in Genetics, 2025)
Mesenchymal stem cells (MSCs) can participate in lymphangiogenesis through paracrine effects, while lymphatic endothelial progenitor cells (LEPCs), a subpopulation of endothelial progenitor cells (EPCs), can differentiate into mature lymphatic endothelial cells, thereby influencing lymphatic function. In the present study, we investigated the mechanism by which MSCs regulate the activity of LEPCs through paracrine effects and preliminarily explored the possibility of the two types of cells working together to treat lymphovascular diseases. After isolation of MSCs and LEPCs from the bone marrow of C57BL/6 J mice, in vitro experiments verified that insulin-like growth factor 1 (IGF-1) secreted by MSCs activated the PI3K/Akt/mTOR pathway to promote the proliferation of LEPCs; IGF-1 decreased the rate of apoptosis and affected the cycle progression of LEPCs and the nucleotide metabolism levels. The therapeutic efficacy of combined transplantation of MSCs and LEPCs was shown to be superior to that of transplantation of LEPCs alone in murine hindlimb lymphedema models. These results suggest that MSCs significantly promote the proliferation of LEPCs through the activation of the PI3K/Akt/mTOR pathway in LEPCs by secreting IGF-1, and that IGF-1 also inhibits apoptosis and regulates cell metabolism. Combined transplantation of MSCs and LEPCs provides an experimental rationale and potential strategy for cell therapy in lymphedema.